The Effect of Origami-based Intervention Therapy on Hallucination Control Among patients with Schizophrenia - Dina Palayukan Singkali; Windu Unggun Cahya Putra; Wirda Wirda; Raden Bagus Edi Santoso; Asmiwarti Abdullah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
Hallucinations are among the most distressing symptoms in schizophrenia, affecting 60–80% of patients and often persisting despite pharmacotherapy. Origami play therapy, a structured fine-motor activity, may improve hallucination control through attention diversion and sensory grounding. This study aimed to determine the effect of origami play therapy on hallucination control ability in patients with schizophrenia. A quasi-experimental one-group pre-post test design was used. The study was conducted at Madani General Hospital, Central Sulawesi, from August to September 2025. Twenty-five inpatients with active hallucinations were selected using purposive sampling. Participants received six 30-minute origami therapy sessions over 14 days. Hallucination control was measured using the Hallucination Control Scale (HCS) before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. The mean hallucination control score increased significantly from 12.4 (SD = 0.71) pre-intervention to 19.2 (SD = 1.38) post-intervention. The median score improved from 12 to 20. The Wilcoxon test revealed a significant improvement (Z = -2.10, p = 0.036). Origami play therapy was associated with significant improvement in hallucination control. However, due to the one-group design without a control group, causality cannot be established. Randomized controlled trials are needed to confirm efficacy before clinical implementation.